Catalisadores NiMo/γ-Al2O3 aditivados com Nb - Atividade para a hidrodessulfurização de tiofeno - Valdés-de-Freitas, Carlos Eduardo (2021)
The burning of fuels in the industry or in vehicle engines is a direct agent in the generation of the atmospheric pollution through the emission of contaminating gases such as NOx and SOx. To minimize this impact, environmental regulations have become increasingly stricter. Thus, the production of clean fuels became of fundamental importance, which has been deeply addressed by the environmental catalysis. Among the most used processes, the hydrodesulfurization (HDS) of hydrocarbons stands out a method in which the sulfur of compounds such as thiophenes, benzothiophenes, dibenzothiophenes, is reduced to H2S. The most used catalysts to this process have as active phase molybdenum (Mo) or tungsten (W) sulfides, promoted by cobalt (Co) or nickel (Ni). The commercial used support is γ-alumina, synthesized by sol-gel, which has a uniform particle size and high specific area. However, with the aim to increase the activity and stability of these catalysts, additives can be added, being niobium one of them, which has shown promising results. In this work, catalysts based on Ni and Mo sulfides were prepared, adding Nb as additive. The precursors were supported via impregnation on γ-alumina prepared by the sol-gel method or via one-pot during the synthesis of that support, with or without the presence of the surfactant CTAB. The metals were incorporated with nominal contents of 4 wt.% of NiO, 18 wt.% of MoO3 and 0.7 wt.% of Nb2O5. The catalysts in their oxide form were characterized by energy dispersive X-ray spectrometry (EDX), X-ray diffraction (including low angle diffraction), nitrogen physisorption, visible ultraviolet diffuse reflectance spectroscopy (DRS-UVvis) and evaluated at 300ºC in the HDS of thiophene, used as a model molecule. γ-Alumina showed high surface area and pore volume, and that synthesized in the presence of CTAB resulted in a more homogeneous mesopores distribution. XRD data showed an efficient dispersion of the active species on the support, which was confirmed by DRS-UVvis. The HDS of thiophene on the studied catalysts confirmed the promoting effect of Ni on the Mo activity and a promising impact of Nb as an additive, which increased the activity of the NiMo catalyst.